Unanesthetized Rodents Demonstrate Insensitivity of QT Interval and Ventricular Refractory Period to Pacing Cycle Length - Mulla, Wesam; Gillis, Roni; Murninkas, Michael; Klapper-Goldstein, Hadar; Gabay, Hovav; Mor, Michal; Elyagon, Sigal; Liel-Cohen, Noah; Bernus, Olivier; Etzion, Yoram (Frontiers in Physiology, 2018)
Aim: The cardiac electrophysiology of mice and rats has been analyzed extensively, often in the context of pathological manipulations. However, the effects of beating rate on the basic electrical properties of the rodent heart remain unclear. Due to technical challenges, reported electrophysiological studies in rodents are mainly from ex-vivo preparations or under deep anesthesia, conditions that might be quite far from the normal physiological state. The aim of the current study was to characterize the ventricular rate-adaptation properties of unanesthetized rats and mice. Methods: An implanted device was chronically implanted in rodents for atrial or ventricular pacing studies. Following recovery from surgery, QT interval was evaluated in rodents exposed to atrial pacing at various frequencies. In addition, the frequency dependence of ventricular refractoriness was tested by conventional ventricular programmed stimulation protocols. Results: Our findings indicate total absence of conventional rate-adaptation properties for both QT interval and ventricular refractoriness. Using monophasic action potential recordings in isolated mice hearts we could confirm the previously reported shortening of the action potential duration at fast pacing rates. However, we found that this mild shortening did not result in similar decrease of ventricular refractory period. Conclusions: Our findings indicate that unanesthetized rodents exhibit flat QT interval and ventricular refractory period rate-dependence. This data argue against empirical use of QT interval correction methods in rodent studies. Our new methodology allowing atrial and ventricular pacing of unanesthetized freely moving rodents may facilitate more appropriate utility of these important animal models in the context of cardiac electrophysiology studies.